THE IMPORTANCE OF INNOVATIVE ECONOMIC MEASURES IN FORMING THE COMPETITIVE ENVIRONMENT - Oltaev Sh.S (TADQIQOTLAR, 2026)
Abstract: this article examines the importance of innovative economic measures in the formation of a competitive environment. The article also examines the essence of the competitive environment in the country’s economy and the importance of economic measures taken in its formation, the effectiveness of privileges and preferences that determine the directions of economic development in a market economy, and the priority principles of development programs based on international experience. Reforms aimed at developing a competitive environment at the current stage of the Uzbek economy are studied.